2015
DOI: 10.1016/j.rinp.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the total electron content absolute value from the GPS/GLONASS data

Abstract: a b s t r a c tWhen determining the absolute oblique total electron content (TEC) of the ionosphere using both GLON-ASS/GPS code and phase measurements, there occurs a systematic error associated with the differential code biases (DCBs). A 1-ns DCB leads to the $2.9 TECU error when determining L1-L2 dual-frequency oblique TEC. We have developed an algorithm for DCB estimation from the data of a single GPS/GLONASS station. Presented are the results of the algorithm operation compared with the oblique TEC correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 6 publications
1
16
0
6
Order By: Relevance
“…We used global ionospheric maps to confirm global effects, and to estimate the regional effects over Mexico we used local data. Receiver‐independent exchange files provided by different regional networks of GPS receivers were processed by TayAbsTEC method (Mylnikova et al, ; Yasyukevich, Mylnikova, & Polyakova, ; Yasyukevich, Mylnikova, Kunitsyn, et al, ). Note that it is challenging to separate the effects of different space weather phenomena in September 2017, since several of them overlap and occurred within a few days.…”
Section: Space Weather Observations In Mexicomentioning
confidence: 99%
“…We used global ionospheric maps to confirm global effects, and to estimate the regional effects over Mexico we used local data. Receiver‐independent exchange files provided by different regional networks of GPS receivers were processed by TayAbsTEC method (Mylnikova et al, ; Yasyukevich, Mylnikova, & Polyakova, ; Yasyukevich, Mylnikova, Kunitsyn, et al, ). Note that it is challenging to separate the effects of different space weather phenomena in September 2017, since several of them overlap and occurred within a few days.…”
Section: Space Weather Observations In Mexicomentioning
confidence: 99%
“…It is known, that the mapping function influences a lot on the accuracy of the absolute vTEC estimation [Schaer et al 1998]. After analyzing mapping functions for a number of observation points using the stations of IGS network and simulations based on IRI-2012 the authors [Mylnikova and Yasyukevich 2016, Yasyukevich et al 2015a, Yasyukevich et al 2015b showed that the changes of sTEC occurred with different velocities in various regions of the Earth due to different angles of the satellite passage at different latitudes. They introduced experimentally-determined correction factors α to convert sTEC to vTEC.…”
Section: Tayabstec Vtecmentioning
confidence: 99%
“…-estimation of the limited bandwidth of a wideband system (coherent bandwidth) for the case of operation of a communication system in a dispersive channel [5,6]; Effect of frequency dispersion cannot be completely eliminated if TEC is measured with an error. When measuring TEC based on data from navigation satellites [7], stochastic errors occur. As a result, the measured TEC value can be written as follows:…”
Section: Computational-experimental Methods Of Diagnosing Frequency DImentioning
confidence: 99%